OPTIMALISASI AKUNTABILITAS ORGANISASI PELATIHAN PEMBUKUAN SEDERHANA DAN PENYUSUNAN LAPORAN KEUANGAN DI AMGPM CABANG ELIM I - Simanjuntak, Pranatalindo; Talla, Alend; Boki, Emi; Tamayani Tjio, Sari; Zahra, Zahra; Piterson Radjawane, Erik (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This service research aims to increase the accountability and transparency of financial management at AMGPM Elim I Branch through simple bookkeeping training and preparation of financial statements. The method used is Participatory Action Research (PAR) with a mentoring approach, which actively involves organizational administrators in problem identification, program design, and evaluation of results. Activities are carried out through interactive lectures, transaction recording simulations, report preparation practices, and assistance in the use of digital templates. The results of the study showed that there was an increase in participants' understanding of the basic accounting cycle, technical skills in compiling simple reports, and awareness of the importance of transparency and ethics in the financial management of non-profit organizations. Participants are also able to apply simple technology-based bookkeeping independently. Overall, the program contributes to strengthening organizational governance and building a culture of sustainable accountability.